2015
DOI: 10.1007/s11064-015-1652-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Cytosolic Calcium Regulate the Neuronal Malate–Aspartate NADH Shuttle: Implications for Neuronal Energy Metabolism

Abstract: The malate-aspartate NADH shuttle (MAS) operates in neurons and other cells to translocate reducing equivalents from the cytosol to the mitochondrial matrix, thus allowing a continued flux through the glycolytic pathway and metabolism of extracellular lactate. Recent discoveries have taught us that MAS is regulated by fluctuations in cytosolic Ca 2? levels, and that this regulation is required to maintain a tight coupling between neuronal activity and mitochondrial respiration and oxidative phosphorylation. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…In our minds, the current literature and the biochemical design of neurons and astrocytes are largely consistent with a situation according to which both neurons and astrocytes contribute to the surge in extracellular lactate during brain activation; either cell type may then consume lactate when available or the lactate may be dispersed and metabolised elsewhere or even leave the brain (Madsen et al 1999;Hertz et al 2014;Satrustegui & Bak, 2015). The cellular location and timing of lactate synthesis and consumption in the brain in health and disease largely remains an open question that deserves to be investigated with an open mind.…”
Section: Final Thoughtssupporting
confidence: 52%
See 1 more Smart Citation
“…In our minds, the current literature and the biochemical design of neurons and astrocytes are largely consistent with a situation according to which both neurons and astrocytes contribute to the surge in extracellular lactate during brain activation; either cell type may then consume lactate when available or the lactate may be dispersed and metabolised elsewhere or even leave the brain (Madsen et al 1999;Hertz et al 2014;Satrustegui & Bak, 2015). The cellular location and timing of lactate synthesis and consumption in the brain in health and disease largely remains an open question that deserves to be investigated with an open mind.…”
Section: Final Thoughtssupporting
confidence: 52%
“…; Hertz et al . ; Satrustegui & Bak, ). The cellular location and timing of lactate synthesis and consumption in the brain in health and disease largely remains an open question that deserves to be investigated with an open mind.…”
Section: Why Is This Issue Worth a Crosstalk Debate?mentioning
confidence: 99%
“…However, it remains to be learned whether this correlation is produced by a direct modulation of glycolytic rate by cytosolic calcium (e.g. Singh et al, 2004; Kim et al, 2016; Nicholson-Fish et al, 2016; Hu et al, 2016), by indirect effects due to Ca 2+ uptake by mitochondria (Duchen, 1992; Satrústegui and Bak, 2015), or simply by the ATP burden produced by the demands of Ca 2+ extrusion.…”
Section: Discussionmentioning
confidence: 99%
“… 37 showing that glutamate does not trigger Glucose utilization but rather inhibits Glucose transport and utilization in neurons. In contrast, other studies showed that neuronal depolarization is accompanied by an increase in cytosolic NADH/NAD + ratio that is associated with a reduction of the malate-aspartate shuttle activity through the glycolytic pathway 38 . It was also observed that Glucose utilization is positively correlated with intracellular Ca 2+ signaling whereas L-Lactate utilization is not 24 , 39 .…”
Section: Discussionmentioning
confidence: 79%